The Influence of Financial Literacy, Financial Behavior, and Emotional Intelligence on Investment Decisions in the Capital Market for Generation Z in the City of Surabaya - Adellia Audrey Lovelyzia; Irantha Hendrika Kenang (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This research aims to test and analyze the influence of financial literacy, financial behavior and emotional intelligence on investment decisions for generation Z in the city of Surabaya. This research uses a quantitative research approach with multiple linear regression analysis methods with a total of 190 samples who are capital market investors in the city of Surabaya with a generation Z background. The results of the research show that: (1) Financial literacy negatively and significantly influences capital market investment decisions in generation Z in the city of Surabaya; (2) Financial behavior positively and significantly influences capital market investment decisions among generation Z in the city of Surabaya; (3) Emotional intelligence negatively and significantly influences capital market investment decisions in generation Z in the city of Surabaya.